A comparative evaluation of treatment methods for bile duct stones after hepaticojejunostomy between percutaneous transhepatic cholangioscopy and peroral, short double-balloon enteroscopy. (January 2017) - Tsutsumi, Koichiro; Kato, Hironari; Yabe, Shuntaro; Mizukawa, Sho; Seki, Hiroyuki; Akimoto, Yutaka; Uchida, Daisuke; Matsumoto, Kazuyuki; Tomoda, Takeshi; Yamamoto, Naoki; Horiguchi, Shigeru; Kawamoto, Hirofumi; et al.
Background: Bile duct stones after hepaticojejunostomy are considered a troublesome adverse event. Although percutaneous transhepatic procedures using a cholangioscopy is performed to treat these bile duct stones, a peroral endoscopic procedure using a short, double-balloon enteroscope (sDBE) is an alternative. This study aimed to compare the immediate and long-term outcomes of both treatments for bile duct stones in patients who underwent prior hepaticojejunostomy. Methods: Between October 2001 and May 2013, 40 consecutive patients were treated for bile duct stones after hepaticojejunostomy at a tertiary care hospital. Initial success with biliary access, biliary intervention-related technical success, clinical success, adverse events, hospitalization duration, and stone-free survival were retrospectively evaluated. Results: The initial success rates for biliary access were 100% (8/8) with percutaneous transhepatic cholangioscopy (PTCS) and 91% (29/32) with sDBE. In three patients in whom biliary access during initial sDBE failed, successful access with subsequent PTCS was achieved, and biliary intervention-related technical success and clinical success were eventually achieved in all 40 patients. The rate of adverse events was significantly lower with sDBE than with PTCS (10% versus 45%; p = 0.025). The median hospitalization duration for complete stone clearance was significantly shorter with sDBE than with PTCS (10 versus 35 days; p < 0.001). During the median 7.2 year or 3.1 year follow up, the probabilities of being stone-free at 1, 2, and 3 years were 100%, 73%, and 64% for PTCS and 85%, 65%, and 59% for sDBE, respectively ( p = 0.919). Conclusions: sDBE was useful, with few adverse events and short hospitalization; therefore, experienced endoscopists can consider it as first-line treatment for bile duct stones in patients with prior hepaticojejunostomy.